Quality attributes of chevon patties incorporated with camel milk protein hydrolysates. Issue 2 (13th March 2017) - Kumar, Devendra; Chatli, Manish Kumar; Singh, Raghvendar; Mehta, Nitin; Kumar, Pavan
Abstract : Purpose: The purpose of the present study was to investigate the effect of camel milk protein hydrolysates (CMPHs) on physico-chemical, sensory, colour profile and textural quality attributes of chevon patties. Design/methodology/approach: Camel milk proteins were hydrolyzed with three different proteolytic enzymes, viz., alcalase (CMPH-A), α-chymotrypsin (CMPH-C) and papain (CMPH-P), and dried to powder form before further utilization. Four treatments were prepared with incorporation of CMPH, viz., CMPH 0 per cent (C), CMPH-A 0.09 per cent (T1 ), CMPH-C 0.06 per cent (T2 ) and CMPH-P 0.09 per cent (T3 ), in the product formulation. The developed goat meat patties were evaluated for physico-chemical (pH; emulsion stability, ES; cooking yield, CY; water activity, aw ), instrumental colour and texture profile and sensory attributes. Findings: The pH, moisture, fat and ES values of goat meat emulsions were comparable amongst treatments as well as with the control; however, treated emulsions had higher ES and moisture content. The pH and moisture per cent of cooked chevon patties varied significantly, whereas other physico-chemical (CY, aw, per cent protein, per cent fat, per cent ash and per cent dietary fibre) as well as dimensional parameters (per cent gain in height and decrease in diameter) were comparable amongst treatments and the control. Hardness, springiness, stringiness, cohesiveness, gumminess and resilience of chevon patties decreased significantly ( p < 0.05) with the incorporation of CMPH than that of the control; however, the values were comparable among all the treated products. Protein hydrolysate in chevon patties resulted in significant increase in redness (a*) values, whereas all other parameters (L*, b* and hue) decreased significantly as compared to that of the control. The colour and appearance, texture, juiciness overall acceptability scores were comparable in all the treated products and were significantly ( p < 0.05) higher than the control. The flavour scores of C, T1 and T3 were comparable but significantly lower than that of T2 . The overall acceptability scores of T1 and T2 were also comparable and significantly higher than C and T3 ; however, the highest score was recorded for T2 . Practical implications: Results concluded that chevon patties with acceptable sensory attributes and improved CY and textural attributes can be successfully developed with the incorporation of CMPH. Originality/value: The protein hydrolysates of different food proteins could be explored in a same pattern to find out their implication in food matrices.